Pengaruh Investment Opportunity Set, Liquidity, dan Corporate Social Responsibility terhadap Cash Holding - Mikyal Farialmira; Nuramalia Hasanah; Aji Ahmadi Sasmi (Jurnal Akuntansi, Perpajakan dan Auditing, 2024)
The objective of this research is to investigate and evaluate the results of Investment Opportunities Set, Liquidity, and Corporate Social Responsibility on Cash Holding. This study uses purposive sampling to select samples, using secondary data sources derived from the company's annual report and sustainability report for the period 2020 to 2022, non-cyclical sector companies are being included on the Indonesia Stock Exchange (IDX). The final number of samples obtained was 52 companies with a total observation of 145 data. EViews 12 software is used to perform panel data regression analysis during data processing. The hypothesis of this study was tested and found that corporate social responsibility does not affect cash holding, while investment opportunity set and liquidity have an affect on cash holding.